Comparison of scleractinian coral reproduction and recruitment on tropical (Reunion) and subtropical (South Africa) reefs in the south Western Indian Ocean - (:unkn) unknown (My University, 2014)
Coral reproduction and recruitment in Scleractinia were compared between the subtropical reefs of South Africa and the tropical reefs of Reunion to assess variations between contrasting environments. In addition, coral larvae and juvenile polyps were exposed to elevated temperature in aquarium to simulate global warming. The two targeted species, Acropora austera and Platygyra daedalea, exhibited the same reproductive mode (hermaphroditic broadcast spawner), gamete development (5-6 months) and breeding seasonality (October to February) in South Africa and Reunion. Coral fecundity was nevertheless higher in South Africa than in Reunion. A. austera and P. certaine limite.AbstractCoral reproduction and recruitment in Scleractinia were compared between the subtropical reefs of South Africa and the tropical reefs of Reunion to assess variations between contrasting environments. In addition, coral larvae and juvenile polyps were exposed to elevated temperature in aquarium to simulate global warming. The two targeted species, Acropora austera and Platygyra daedalea, exhibited the same reproductive mode (hermaphroditic broadcast spawner), gamete development (5-6 months) and breeding seasonality (October to February) in South Africa and Reunion. Coral fecundity was nevertheless higher in South Africa than in Reunion. A. austera and P. daedalea produced respectively 43 and 100% more oocytes per polyp than their Reunion counterparts. The recruitment rate was also higher on the subtropical reefs of South Africa (548 recruits m2 year-1) compared to Reunion (305 recruits m2 year-1). Recruitment was dominated by Pocilloporidae at the two localities, followed by Acroporidae in South Africa and Poritidae in Reunion. In South Africa, an increase in sea temperature of 2°C strongly affected the larval development of the sensitive A. austera, while the more robust P. daedalea sustained temperatures up to 4°C (i.e. 30°C) above ambient. In Reunion, diminished fecundity an
Keywords: African Research